Organic fertilization with three levels of chicken manure in four potato cultivars - Perez López, Delfina de Jesús; Monroy, Josué Peñaloza; Reyes Ramírez, Ana Karen; Huerta, Andrés González; Sangermán Jarquín, Dora Ma. (Revista Mexicana de Ciencias Agrícolas, 2019)
The present work was carried out in the spring-summer cycle of 2017 in Ojo de Agua, municipality of Zinacantepec, State of Mexico, to evaluate the response of three levels of chicken manure and a chemical fertilization treatment in four potato cultivars. The 16 treatments were evaluated in a randomized complete block design in a 4x4 factorial arrangement with three replications. The size of the experimental plot was integrated with three furrows 4 m long and 0.90 m wide. The registered variables were plant height, number of stems and tubers per plant, tuber weights per plant, fresh foliage, harvest index, yield per hectare, diameter (DT) and tuber length (LT). The results showed that the cv. Rosita (24.38 t ha-1) and Ágata (23.85 t ha-1), in 4 t ha-1 of chicken manure, produced the highest tuber yields. Major components 1 and 2 explained 69.19% of the original total variation. In 4 t ha-1 of chicken manure there were more stems and greater weights of tuber, foliage in fresh and tuber production. The cv. Rosita and Ágata excelled in stems per plant, as well as tuber weights and fresh foliage; the first had more tubers per plant. In the cv. Fianna, Ágata and Lucero recorded the highest harvest rates.